Tradução para o português brasileiro, adaptação transcultural e validação do 3D Assessment of Hand Function - Cortopassi, Andrea Christina [UNESP] (2015)
Introduction: In recent decades the assessment of health status by the patient has been prioritized over the assessment only the doctor's point of view. Quality of life related to health, functional capacity, pain scales and satisfaction have been emphasized by allow for an analysis of the health situation and the symptoms of the disease in the individual's life in their own perspective, complementing the clinical and objective data. The 3D Assessment of Hand Function is a questionnaire which assesses pain, function and appearance in patients with diseases of the hands, quick and easy application. Objectives: Translate into Brazilian Portuguese, perform the cross-cultural adaptation and validation of the assessment tool of hand pathologies 3D Assessment of Hand Function. Methods: The questionnaire was translated and adapted to the Brazilian populations according to internationally recommended methods, was subsequently applied in the pre-test phase the 30 patients with injuries on the hands. After analyzing the difficulties observed in the pre-test, was generated the final version in Portuguese. This version was administered to 220 patients. The validation was performed through test and retest in 23 patients. The translation data were analyzed descriptively, the test and retest reliability by intraclass correlation coefficient (ICC) and the Kappa coeficiente and the internal consistency Cronbach's Alpha. Results: Some expressions have been adapted to the Brazilian population, as instrument of presentation showed some changes to better understanding of it. Regarding the internal consistency of results in the overall assessment of all items, Cronbach's alpha was 0.608 considered reasonable, the intraclass correlation coefficient values (ICC) for item 1(function) of 0.796 with a confidence interval (CI) of 95% (0.519 to 0.913); item 2 (pain) of 0.880 95% CI (0.670 to 0.941) and item 3 (appearance) of 95 0.907% (0.781 to 0.961). The Kappa ...